Which are the best predictors of theory of mind delay in children with specific language impairment?. Issue 6 (1st August 2013) - Andrés‐Roqueta, Clara; Adrian, Juan E.; Clemente, Rosa A.; Katsos, Napoleon
Abstract: Background: The relationship between language and theory of mind (ToM) development in participants with specific language impairment (SLI) it is far from clear due to there were differences in study design and methodologies of previous studies. Aims: This research consisted of an in‐depth investigation of ToM delay in children with SLI during the typical period of acquisition, and it studied whether linguistic or information‐processing variables were the best predictors of this process. It also took into account whether there were differences in ToM competence due to the degree of pragmatic impairment within the SLI group. Methods & Procedures: Thirty‐one children with SLI (3;5–7;5 years old) and two control groups (age matched and language matched) were assessed with False Belief (FB) tasks, a wide battery of language measures and additional information‐processing measures. Outcomes & Results: The members of the SLI group were less competent than their age‐matched peers at solving FB tasks, but they performed similarly to the language‐matched group. Regression analysis showed that overall linguistic skills of children with SLI were the best predictor of ToM performance, and especially grammar abilities. No differences between SLI subgroups were found according to their pragmatic level. Conclusions & Implications: A delay in ToM development in children with SLI around the critical period of acquisition is confirmed more comprehensively, and it is shown to be more strongly related to their general linguistic level than to their age and other information‐processing faculties. This finding stresses the importance of early educational and clinical programmes aimed at reducing deleterious effects in later development.